Latar Belakang Tindakan Kenakalan Anak pada Usia 13 sampai 17 Tahun - Nina Siti Salmaniah Siregar (Universitas Medan Area, 2015)
This study aims to determine the factors that cause actions Delinquency child, family influences the child's misbehavior, and the community's role in tackling the problem of delinquency in the village of Lau Cih district of Medan Tuntungan. This study uses qualitative descriptive by the number of all children aged population is aged 13 -17 years totaling 65 people. Then the sample in this study is taken whole from the total population that is numbered 65 people or also called total sample. In the process of collecting data the author uses observation, questionnaires, and interviews. To analyze the data that have been collected in this research is to use a frequency table with a percentage formula. From the results of research in the field after the data are collected, processed and analyzed, then produce research findings that background action delinquency is due to lack of attention and supervision from parents where parents who are too busy with work so that children no longer receive the attention and affection of family. Aside from the family environment, community environment is also one of the factors that affect the child. Where the child's living environment is not a good environment for your children, so that children are affected and take action delinquency without warning and awareness of the local community.